Pengaruh Budaya Organisasi terhadap Kinerja Pegawai yang Dimediasi oleh Komitmen Kerja Kantor Pengawasan dan Pelayanan Bea Dan Cukai Tipe Madya Cukai Malang - Oktapianus Oktapianus; Endi Sarwoko; Dianawati Suryaningtyas (Jurnal Riset Mahasiswa Manajemen, 2018)
Human resources are a very important part for a company in developing its performance. Because in the world of work, human resources are needed professionally. Then the competition for human resources who have diverse abilities in the world of work is increasing. Factors that also affect employee performance are organizational culture and work commitment. The implementation of an organizational culture in an organization will be able to encourage someone to be able to take ethical actions. Work commitment can be used as an indicator to measure employee turnover in a company. The purpose of this research is to examine the influence of organizational culture on work commitments and to examine the influence of organizational culture on employee performance through work commitments (Office of Supervision and Service of the Middle and Excise Type of Malang Excise). This type of research is quantitative. Then using a random sampling technique. This study used a sample of 74 respondents taken from the employees of the Office of Supervision and Service of Customs and Excise Type, Malang Excise. Scales of measurement in this study use a Likert scale. The results of this study indicate that there is a significant influence between organizational culture on work commitment, there is an indirect effect between organizational culture on employee performance through work commitment.